Maternal health services for pregnant adolescent girls in Uganda: Barriers and Opportunities - Namuli, Vivian; Chinkonono, Gorgeous Sarah; Atuhaire, Catherine; Christensen, Betty Nyawira; Pemunta, Vitalis; Cumber, Samuel Nambile (Research square, 2020)
Background: Globally, adolescent pregnancy is one of the major areas of concern. Over 16 million girls aged between 15-19 years give birth, while over 1 million become pregnant before 15 years, most of who are in Sub-Saharan Africa. Yet, very few adolescents access maternal health services. This study explored the available maternal health services, barriers in accessing them and possible strategies for improving accessibility to these services among pregnant adolescents, specifically in Uganda. Methods: The study was carried out at Naguru teenage information and health Centre (NTIHC), Nakawa division, Kampala district using a qualitative research approach. Data was obtained using in-depth face to face interviews from 31 independent pregnant adolescents and four health care providers. These participants were selected using convenient sampling technique. Data was manually analyzed and themes were extracted and used in the interpretation of results. Results: The study found out that adolescents use only antenatal health care services while the uptake of postpartum health services was side-lined much as they were found available in the health facilities. The dominant antenatal care services among adolescents include; testing and managing of STIs, measuring pressure, tetanus vaccine, measuring weight, counselling and guidance, peer education, and providing drugs. Adolescents also encountered challenges such as long distances, financial constraints, stigmatization, negative attitude of health workers and community expressed bias when accessing these services. It further revealed that through government intervention, community and health workers, accessibility to maternal health services would be improved. Specifically, increasing remuneration for health workers; sensitizing communities about adolescent pregnancy and rights; construction of labour suites; and health workers’ competence were highly emphasized. Conclusion: Advertising and promotion of maternal health services; sensitization of community members; and government involvement will be the key parameters for enhancing maternal health care among adolescent mothers.
Keywords: Adolescent pregnancy; Health care accessibility; Maternal health services